SISTEM PEREKONOMIAN 3 SEKTOR DAN 4 SEKTOR - Shafa Azalia Putri; Rolan Rizky Rinaldi Daulay; T. Rahma Rindiany; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The three-sector and four-sector economic systems are the primary analytical frameworks for understanding national income flows. The three-sector model involves households, firms, and the government. This model explains the state's role in tax collection, public spending, and economic stabilization. The four-sector model adds a foreign sector. This addition broadens the analysis through exports, imports, and international capital flows. This study aims to analyze the differences in structure, mechanisms, and economic implications of the two systems for national income balance. The method used is a literature review with a descriptive-analytical approach based on Keynesian macroeconomic theory. The results of the study indicate that the three-sector system is effective in explaining fiscal policy in a closed economy. The four-sector system is more relevant for an open economy integrated with global trade. In conclusion, the selection of an economic model must be tailored to the characteristics of a country's economic structure to ensure more accurate and applicable policy analysis.